2007
DOI: 10.2165/00019053-200725030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cost Effectiveness of Insulin Glargine for the Treatment of Type 1 and 2 Diabetes in Canada

Abstract: The cost-effectiveness ratios for insulin glargine use for type 1 and 2 diabetes provide evidence for its adoption from a Canadian healthcare payer perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…The results suggest that insulin detemir can be considered a cost-effective treatment alternative to NPH insulin over a one year period in all four countries analysed. These findings are consistent with long-term modelling studies that have compared the economic benefit of insulin analogues and NPH insulin in the treatment of T2DM [44][45][46] .…”
supporting
confidence: 88%
“…The results suggest that insulin detemir can be considered a cost-effective treatment alternative to NPH insulin over a one year period in all four countries analysed. These findings are consistent with long-term modelling studies that have compared the economic benefit of insulin analogues and NPH insulin in the treatment of T2DM [44][45][46] .…”
supporting
confidence: 88%
“…35,59,60 For example, the incremental cost per quality-adjusted life-year estimated by Grima and colleagues 59 for insulin glargine in patients with type 1 diabetes increased from Can$20 799 to Can$87 132 when effect sizes of hemoglobin A 1c were decreased from 0.40% to 0.20%. 59 When fear of hypoglycemia was included in an evaluation by the National Institute of Clinical Excellence in London, England, the incremental cost per quality-adjusted lifeyear for insulin glargine compared with neutral protamine Hagedorn insulin was reduced from £32 000 to £3500 for type 1 diabetes and from £120 000 to £32 500 for type 2 diabetes. 60 The Center for Outcomes Research Diabetes Model 6 accommodates fear of hypoglycemia by applying a chronic decrement to health-related quality-of-life scores in the conventional-insulin arm only.…”
Section: Limitationsmentioning
confidence: 99%
“…(16) One CUA found that iDet was dominant (less costly and more effective) over iGlarg, (44) while another found that iGlarg was the dominant option when compared to iDet. (16) The results of our economic analysis are in line with the findings from some of these previously published cost-utility analyses, which found that iDet was cost effective compared to iNPH (ICERs: £2,500, £3,443, £9,526, £12,989 and £19,285 per QALY gained), (18;20;42-44) iGlarg was cost effective compared to iNPH (ICERs: £3,496 -£4,978, £3,189 -£9-767 and £10,903 per QALY gained), (45)(46)(47) and one study finding that iDet was dominant (less costly and more effective) over iGlarg. (44) However, this last analysis and ours conflict with that of Cameron and colleagues, (16) which concluded that iGlarg dominated iDet.…”
Section: Discussionmentioning
confidence: 77%
“…(16) Three CUAs found that iGlarg was cost effective compared to iNPH, (45)(46)(47) another found that iGlarg was dominant compared to iNPH,(48) while another found that iGlarg was not cost effective compared to iNPH. (16) One CUA found that iDet was dominant (less costly and more effective) over iGlarg, (44) while another found that iGlarg was the dominant option when compared to iDet.…”
Section: Discussionmentioning
confidence: 99%